Can Patios Make Cities? Urban Traces of TPA in Brazil and Venezuela - Barrios, Carola (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
In August 1953 city planners José Luis Sert and Paul Lester Wiener –founders of TPA (Town Planning Associates) with their practice in New York City– published an urban manifesto in the journal Architectural Forum entitled: Can Patios Make Cities? In this article Wiener& Sert sustain that patios, the very ancient architectural device of Latin American cities, can become a typological key element in the conception and design of modern cities. [Fig. 1] Mainly illustrated with drawings for the city-plans designed by TPA in Brazil, Venezuela and Cuba, according to the authors, their experience in Latin America should be taken by the community of U.S. planners “not as a working model to be copied, but as a kind of laboratory model against which to check our own ideas”1 in direct response to the discussions set up by CIAM (Congrès International d’Architecture Moderne) immediately after World War II. This study provides an account of the exploratory model of compact-planning undertaken by Sert & Wiener, not in the master plans developed for existing cities in Latin America, but in the common ground of the inter-tropical essays designed for three entirely new towns: Cidade dos Motores (Brazil, 1944-47), Ciudad Piar and Puerto Ordaz (Venezuela, 1951-53). Based on different documentary sources to support our work we will examine the urban design principles practiced by TPA in these cities within the multilayered dynamics of war and the expansion of air transportation in Latin America.
Keywords: Post World War II Planning; TPA; patio; Compact-Planning; Brazil; Venezuela